Calculation of Roundabouts Capacity, Waiting Phenomena and Reliability - Mauro, Raffaele; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Roundabouts have become one of the most significant traffic control measures because they are generally statistically safer and more efficient than traditional at grade intersections. This book is dedicated to the evaluation of the operating conditions of roundabouts. In five parts, it thoroughly illustrates the calculation of the capacity,including reliability, and waiting phenomena parameters, such as the times spent in the system and queue lengths. Fully worked examples are included throughout the chapters, with detailed explanations.
Calculation of Roundabouts: Problem Definition -- Capacity Evaluation -- Waiting Phenomena at Steady State and Non-steady State Conditions -- Calculation of Waiting Times, Queue Lengths, and Levels of Service -- Evaluation of Roundabout Reliability.
Keywords: Engineering; Regional planning; Architecture; Engineering economy; Civil engineering; Engineering; Civil Engineering; Landscape/Regional and Urban Planning; Urbanism; Engineering Economics, Organization, Logistics, Marketing